Pelatihan Kader Posyandu dalam Meningkatkan Pengetahuan dan Keterampilan Deteksi Dini Risiko Tinggi (DDRT) pada Ibu Hamil - Nurmisih, Nurmisih; Pulungan, Verawati (Universitas Baiturrahim, 2025)
High-risk pregnancies are a major contributor to maternal and fetal morbidity and mortality. This community service aimed to increase the knowledge and skills of Posyandu cadres in detecting high-risk pregnancies through structured education and simulation using the KSPR tool. Activities involved 20 cadres and 20 pregnant women in Suka Maju village. Pretest and posttest evaluations showed an increase in average knowledge scores from 9.85 to 13.30 and skills from 42.00 to 87.00. The activity was proven effective in empowering community health volunteers to contribute actively in early risk detection